Abramović – Ulay 1980–1988: Desert Storm Survivors - Racanović, Svetlana (Poznańskie Studia Slawistyczne, 2017)
The twelve-year collaborative practice of Marina Abramović and Ulay (Franck Uwe Laysiepen), started with extreme, rapturous and unflinching explorations of capacities of the body in their early performances (a phase they called The Warriors), that corresponded to the fury of the 1970s. In an environment hostile to the living, phenomenological body (in arts, in theoretical discourse) of the 1980s, the two artists recalibrated their living and artistic strategy. During their extensive journeys into distant lands (deserts of Asia, Africa, Australia), they were introduced to and embraced the practices of Eastern meditation techniques, which secured and procured their escape from the limitations of their own culture and their relationship. They also significantly influenced and modified forms and functions of their joint performances. The refined simplicity and stillness of the form of their many-times (re)enacted performance Nightsea Crossing focussed and spurred their inner forces towards self-perfection and the unfolding of more sophisticated lines of connection with the outside, with otherness. The legacy of this performance has affected the direction and function of their later, individual careers.